Beta-induced Alfvén eigenmodes and geodesic acoustic modes in the presence of strong tearing activity during the current ramp-down on JET. (1st April 2022) - Pucella, G; Alessi, E; Auriemma, F; Buratti, P; Falessi, M V; Giovannozzi, E; Zonca, F; Baruzzo, M; Challis, C D; Dumont, R; Frigione, D; Garzotti, L; et al.
Abstract: The analysis of the current ramp-down phase of JET plasmas has revealed the occurrence of additional magnetic oscillations in pulses characterized by large magnetic islands. The frequencies of these oscillations range from 5 to 20 kHz, being well below the toroidal gap in the Alfvén continuum and of the same order as the low-frequency gap opened by plasma compressibility. The additional oscillations only appear when the magnetic island width exceeds a critical threshold, suggesting that the oscillations could tap their energy from the tearing mode (TM) by a non-linear coupling mechanism. A possible role of fast ions in the excitation process can be excluded, being the pulse phase considered in the observations characterized by very low additional heating. The calculation of the coupled Alfvén–acoustic continuum in toroidal geometry suggests the possibility of beta-induced Alfvén eigenmodes (BAEs) rather than beta-induced Alfvén–acoustic eigenmodes. As a main novelty compared to previous work, the analysis of the electron temperature profiles from electron cyclotron emission has shown the simultaneous presence of magnetic islands on different rational surfaces in pulses with multiple magnetic oscillations in the low-frequency gap of the Alfvén continuum. This observation supports the hypothesis of different BAE with toroidal mode number n = 1 associated with different magnetic islands. As another novelty, the observation of magnetic oscillations with n = 2 in the BAE range is reported for the first time in this work. Some pulses, characterized by slowly rotating magnetic islands, exhibit additional oscillations with n = 0, likely associated with geodesic acoustic modes (GAMs), and a cross-spectral bicoherence analysis has confirmed a non-linear interaction between TM, BAE and GAM, with the novelty of the observation of multiple triplets (twin BAEs plus GAM), due to the simultaneous presence of several magnetic islands in the plasma.